An Innovative Movement Mode of Friction and Wear Tester Worktable and Its Application in CMP. (8th October 2021) - Ni, Zifeng; Zhang, Ping; Chen, Guomei; Wang, Yongguang; Qian, Shanhua; Bian, Da; Zhao, Yongwu
Abstract : To improve the reliability of chemical mechanical polishing (CMP) simulation on friction and wear tester, an innovative movement mode of worktable was proposed and optimized. MATLAB was used to simulate the relative movement trajectory under various movement modes. The impact of the worktable movement modes on the evolution of pad surface micro-texture was investigated through friction and wear test. High resolution white light interferometry was used to analyze the pad samples for their surface micro-topography. Finite element analysis was performed to understand the friction process under different movement conditions. The results reveal that with the increase of relative movement trajectory density, the average height and porosity of pad surface decreased, the concentration degree of surface height distribution increased, and the uniformity of pad surface wear was improved gradually. But the porosity of pad surface increased unexpectedly, and surface average height declined rapidly while the period ratio of rectangular cyclic mode to rotational mode raised up to 8:1. The coefficient of friction (COF) was impacted by both material compliance and pad surface flatness. Meanwhile, innovative movement modes of worktable can efficiently reduce the degree of pad deformation and stress concentration while improve the distribution uniformity of friction heat on wafer surface.